(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background/aim: The aim of this study was to determine the expression of CD68, P53 and Bcl2 in thyroid tumors and correlation between them. Materials and Method: The expression of CD68, P53 and Bcl2 was examined by immunohistochemistry on paraffin-embedded tissues obtained from patients with benign and malignant tumors between 2010 and 2015.Thirty three malignant thyroid tumors of variable subtypes and 10 benign tumors. The extents of staining and intensity were scored semi quantitatively. Results: CD68 have shown strong positive score expression in (28.9%) in PTC while score was found in (18.5%). The higher percentage of strong weak positive score expression of P53 was in PTC (6.1%) Followed by (3.03%) strong score in FTC, (3.03%) moderate score in benign and (3.03%) in MTC. The expression of Bcl2 was higher in benign tumors (20%) than in malignant tumors were PTC (9.1%) followed by FTC (3.03%), the strong positive expression seen in MTC (9.1).